Dupilumab efficacy and safety in patients with moderate to severe asthma: A systematic review and meta-analysis - Zaazouee, Mohamed Sayed; Alwarraqi, Asmaa Gomaa; Mohammed, Yasmine Adel; Badheeb, Mohamed A.; Farhat, Abdullah Mohamed; Eleyan, Mohammed; Morad, Afnan; Zeid, Marwa Abdel-Aziz; Mohamed, Aya Shaban; AbuEl-Enien, Hazem; Abdelalim, Ahmed; Elsnhory, Ahmed Bostamy; et al. (Frontiers in Pharmacology, 2022)
Background: Dupilumab is a human monoclonal antibody directed against the alpha subunit of the interleukin-4 receptor and inhibits the signaling of IL-4 and IL-13. It is approved for treating asthma and other type-2 inflammatory diseases. There is a conflict in the literature regarding the safety and efficacy of dupilumab. Thus, we aimed to assess the safety and efficacy of dupilumab in patients with moderate to severe asthma. Methods: Six databases (PubMed, Embase, Scopus, Web of Science, Cochrane library, and clinicaltrials.gov registry) were searched till January 2022. We included randomized controlled trials that compared dupilumab with placebo in moderate to severe asthma patients. We extracted the data at 12 and 24 weeks and analyzed them using review manager 5.4. Findings: Thirteen trials were included. Dupilumab significantly improved the forced expiratory volume in 1 second, asthma control questionnaire score, the fraction of exhaled nitric oxide level, and immunoglobulin E level at 12 and 24 weeks (P < 0.05). However, it was associated with increased blood eosinophils at 12 and 24 weeks. Dupilumab was generally a safe agent for asthmatic patients. It showed no significant difference compared with placebo regarding most adverse events. Conclusion: Dupilumab improves pulmonary function and reduces local and systemic inflammatory markers with minimal adverse events in patients with moderate to severe asthma.